"Biographical Learning" reloaded. Theoretical grounding of a challenging appoach - Alheit, Peter (Adult Education Critical Issues, 2022)
Abstract. This article discusses an apparently ‘outdated’ concept of thinking about learning within the lifespan. Obviously, the term ‘biographical learning’ has been replaced by the label of ‘lifelong learning’. In a first section, this position is critically examined and the importance of the biography for all learning experiences is emphasised. In a second step of argumentation, it is conceptually specified what the peculiarity of biographical learning actually is. The specifity of this learning concept can only be understood from a biographical perspective through the dimensions of ‘temporality’, ‘contextuality’ and ‘reflexivity’. The concluding third part introduces the concept of ‘biographicity’ and proposes a theoretical understanding of the complex biographical learning idea using the ‘grammar metaphor’ from language theory.